PEMBINAAN SASANA TINJU DI SARIO BOXING DI KOTA MANADO - Rafli Bondi Rafli; Ellen B. Lomboan; Nolfie Piri (Labor Program Studi Pendidikan Sosiologi, 2023)
This study aims to reveal how coaching in order to get a boxing athlete who has a winning mentality. My research uses a qualitative approach, which uses information gathering methods through observation, interviews. The results of the study are as follows: (1) Cadre training and Talent Direction, have been running according to what the gym administrators wanted, (2) The training program is determined by the coaches of the Sario boxing boxing gym in accordance with the situation and conditions (3) each trainer is very Playing a role in increasing the performance of a boxing athlete in the gym, even though there are only two coaches who are certified coaches and the rest do not have trainer certificates, and they are former boxing athletes, (4) the facilities and infrastructure in the gym and sario boxing are very adequate ( 5), Community support for the Sario Boxing gym is mostly very very supportive, (6), the achievements of the athletes in the Sario Boxing gym are very good because it can be proven by the achievements they have achieved